PENGARUH KEPEMIMPINAN, KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - Ayu Lestari Wijayanti, Ni Ketut; Subudi, Made (E-Jurnal Manajemen, 2014)
This research was conducted at the Quest Hotel Tuban Bali using all employees as respondents totaling 80 people. Issues contained in the Quest Hotel is a high level of consumer complaint and low employee compensation. The analysis technique used is multiple linear regrsi considering research aims to investigate the influence between independent variables and the dependent variable. This study found that jointly affect leadership and financial compensation simultaneously on employee job satisfaction. Limitations in this study only tested on leadership, financial compensation, employee job satisfaction and performance of employees at Quest Hotel.
Keywords: Leadership, Compensation, Job Satisfaction, Employee Performance